2017
DOI: 10.1159/000452363
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Submucosal Dissection and Endoscopic Mucosal Resection for Non-Ampullary Superficial Duodenal Tumor

Abstract: Background: Endoscopic submucosal resection (ESD) and endoscopic mucosal resection (EMR) are well established as curable and safety procedures for treating superficial tumors of the stomach, esophagus and colon. However, a majority of endoscopic resection strategies for non-ampullary superficial duodenal tumors (NASDTs) remains undefined. The aim of this study was to clarify which was the right method for NASDT treatment - EMR or ESD. Summary: We analyzed 129 consecutive endoscopic resection (74 ESD and 55 EMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
122
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(131 citation statements)
references
References 30 publications
5
122
2
Order By: Relevance
“…To reduce the risk of recurrence, en bloc and complete resection of tumor components is important. ESD is a therapeutic procedure that enables en bloc resection irrespective of lesion size and is superior to EMR in terms of en bloc resection rate and curability [2,27]. An en bloc specimen allows accurate pathological evaluation of risk factors for lymph node metastasis and recurrence and is therefore expected to improve treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the risk of recurrence, en bloc and complete resection of tumor components is important. ESD is a therapeutic procedure that enables en bloc resection irrespective of lesion size and is superior to EMR in terms of en bloc resection rate and curability [2,27]. An en bloc specimen allows accurate pathological evaluation of risk factors for lymph node metastasis and recurrence and is therefore expected to improve treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…ESD, which was developed in Japan, yielded a low recurrence rate (0%) for SNADETs regardless of lesion size [13-17], but this technique was associated with a high incidence of adverse events, including morbid complications (e.g., delayed bleeding, intraoperative perforation, and delayed perforation rates of 0–22%, 19–35%, and 3–20%, respectively) [13-18]. The indication size is ≄15–20 mm, and it is difficult to remove a lesion of this size en bloc using EMR or UEMR Table 1.…”
Section: Characteristics and Treatment Outcome Of Each Er Methodsmentioning
confidence: 99%
“…While several studies have shown the efficacy of endoscopic treatment for NADETs, the procedure is complicated by a high incidence of adverse events due to anatomical reasons [1, 4-7]. In addition, tissue sampling from NADETs through endoscopic forceps biopsy induces fibrosis, which results in difficulty on subsequent endoscopic treatment [8, 9].…”
Section: Introductionmentioning
confidence: 99%